Neurosteroid biosynthesis in the brain of amphibians - Vaudry, Hubert; Do-Rego, Jean-Luc; Burel, Delphine; Luu-The, Van; Pelletier, Georges; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2011)
Amphibians have been widely used to investigate the synthesis of biologically active steroids in the brain and the regulation of neurosteroid production by neurotransmitters and neuropeptides. The aim of the present review is to summarize the current knowledge regarding the neuroanatomical distribution and biochemical activity of steroidogenic enzymes in the brain of anurans and urodeles. The data accumulated over the past two decades demonstrate that discrete populations of neurons and/or glial cells in the frog and newt brains express the major steroidogenic enzymes and are able to synthesize de novo a number of neurosteroids from cholesterol/pregnenolone. Since neurosteroidogenesis has been conserved during evolution from amphibians to mammals, it appears that neurosteroids must play important physiological functions in the central nervous system of vertebrates